2015
DOI: 10.1590/1516-1439.298014
|View full text |Cite
|
Sign up to set email alerts
|

On the Formation of Hydroxyapatite Nano Crystals Prepared Using Cationic Surfactant

Abstract: Being a major constituent of hard tissues found in humans, synthetic hydroxyapatite (HA) as a substitute to natural bone and teeth is gaining importance. In particular, nano hydroxyapatite is expected to impart considerably superior properties. The current research focuses on identification of mechanism of the formation of HA nano-crystals during its preparation when surfactant nano reactors are used for their nucleation and growth. In addition to having a rod-shaped morphology, high resolution electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 24 publications
(26 reference statements)
1
21
0
2
Order By: Relevance
“…The analysis shows round bright patches (holes) distributed randomly in all the particles (Figure b) mostly of size between 11 and 41 nm (Figure 9e), explaining the large surface area obtained from BET analysis. However, even though many studies have reported the presence of sphere‐like nanopores in synthetic apatite, in our case the nanopores are studied in a natural apatite as well as for lamellar aspect. The metal deposition on the particle surface was in a well‐defined nanosphere shape (Figure c) and the Pd nanoparticles were distributed with a mean size of 11.81 nm, as shown in Figure f.…”
Section: Resultsmentioning
confidence: 98%
“…The analysis shows round bright patches (holes) distributed randomly in all the particles (Figure b) mostly of size between 11 and 41 nm (Figure 9e), explaining the large surface area obtained from BET analysis. However, even though many studies have reported the presence of sphere‐like nanopores in synthetic apatite, in our case the nanopores are studied in a natural apatite as well as for lamellar aspect. The metal deposition on the particle surface was in a well‐defined nanosphere shape (Figure c) and the Pd nanoparticles were distributed with a mean size of 11.81 nm, as shown in Figure f.…”
Section: Resultsmentioning
confidence: 98%
“…The characteristic calcium hydroxyapatite absorption bands in the range of 1100-950 cm −1 were clearly visible [32]. Strong bands located at 1035 and 1090 cm −1 resulted from the ν 1 symmetric P-O stretching vibrations in PO 4 3− [32,33]. The broad band visible in the range of 3600-3300 cm −1 is associated with O-H stretch vibrations and attributed to adsorbed water [29,32,34].…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra of pure HAp and HAp−Al 2 O 3 composite are shown in figure 3. The IR band peaks around 3745 and 633 cm −1 correspond to asymmetric OH stretching vibrations [19]. The peaks at 3564 and 3572 cm −1 related to the stretching modes of surface hydroxyl group and absorbed water, respectively [20].…”
Section: Ftirmentioning
confidence: 99%